Contraception - methods, effectiveness and safety - Pawłowska, Paulina; Ozga-Stachurska, Alicja; Wójcik-Grudzień, Justyna; Rozenbajgier, Martyna (Journal of Education, Health and Sport, 2022)
Introduction The article provides an overview of the available methods of contraception, effectiveness, safety, advantages and disadvantages of using a given contraceptive. The use of contraception is becoming more and more popular in society. There are many methods of contraception. The choice depends mainly on the patient’s preferences, but diseases and a well-collected history are also important. The aim of the study Review the latest literature on methods of contraception Material and methods The research was conducted using Articles by PubMed and Google Scholar on methods of contraception Description of the state of knowledge: There are many methods of contraception, Hormonal methods include oral contraceptive pills, contraceptive patches, implants, hormone injections. Barrier products such as copper / levonogestrel IUDs prevent pregnancy by creating a mechanical barrier to prevent conception. [1,2] The most common method - the use of condoms prevents sperm from entering the uterus. All products and methods have benefits and potential complications, therefore the method should be selected individually for each patient. [6,7] Summary: There are many types of contraception . Some of them are almost 100% effective in preventing pregnancy. [1,3,4,5,] It should be remembered that each method of contraception should be selected individually, depending on the patient’s needs. [8,9]